Gambaran kadar kolesterol dan pola makan suku anak dalam di Desa Bukit Suban dan Sekamis Kabupaten Sarolangun tahun 2016 - maria estela karolina (Riset Informasi Kesehatan, 2017)
Background: Cholesterolemia is one of global health problem, associated with coronary heart disease and compounded by unhealthy dietary habit. Suku Anak Dalam with a primitive lifestyle, has not been affected by modernization, not eat junk food, eating only food from hunting and farming itself, and smoking is intresting factor for doing the research. The purpose of this research is to describe the levels of cholesterol and dietary habit to Suku Anak Dalam in Bukit Suban and Sekamis villages. Methods: Thisis descriptive research. There is 44respondents by Systematic Random Sampling technique calculation. The research was conducted in Bukit Suban and Sekamis village at Sarolangunin 2016. The data were obtained from blood samples and conducting interviews. Results: The results showed that 79.5% had abnormal cholesterol levels, 45.45% of children-adolescent group had normal cholesterol levels, 40.91 % female gender group had normal cholesterol levels, 45.45% are not married have normal cholesterol levels, 50% eat two times a day, 59.1% consumerice as staple food, 36.4% consume animal chicken and fish as well as chicken and pork, 59.1% consume tempe and tofu, 4 people 31.4% consume vegetables that are spinach and kale, 45.5% consume Banana. Conclusion: The conclusion of this study is that the majority of Suku Anak Dalam have normal cholesterol levels with diet varied. Keywords: Cholesterol, Dietary Habit, Suku Anak Dalam.